Is compensation and work environment a trigger for job satisfaction? Empirical Study on CV Saba Footwear Tangerang - Kurniawati, Tati; suranah, Suranah; Rahmawati, Novita; Haryadi, Didit; wahyudi, Wahyudi (International Journal of Applied Finance and Business Studies, 2024)
Job satisfaction is the feeling that every employee has about pleasure in their job, which is obtained from job evaluations—effective management thinking about the importance of human resources. Employee job satisfaction is an important factor influencing success. In an organization, this is one of the most important functions of a company. This study aims to determine the variables that affect employee job satisfaction and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with 30 respondents drawn into samples using non-probability sampling and saturated sampling / total sampling. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that employee job satisfaction cannot be affected by compensation because compensation has been in line with employee expectations. The second hypothesis states that the work environment influences employee job satisfaction. The third hypothesis is that employee performance is influenced by employee compensation and work environment, which can simultaneously increase employee job satisfaction. This research is expected to provide theoretical contributions to the literature in this context, certainly in the context of human resource management